Measuring Environmental Awareness of Prospective Physics Teachers: Validation of an Environmental Attitude Instrument - Sabaruddin, Sabaruddin; Prasetyo, Zudhan Kun; Mundilarto, Mundilarto; Hafni, Fauriza; Fitriyawany, Fitriyawany (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
Understanding environmental literacy is essential for prospective physics teachers to develop responsible behaviors in responding to environmental changes. However, assessing attitudes toward the environment remains challenging due to the limitations of existing instruments. This study evaluates the feasibility of an environmental affect instrument designed for prospective physics teachers in environmental physics courses. The research employed Thiagarajan’s 4D development model, which consists of four stages: define, design, develop, and disseminate. The instrument was validated by experts and users, with expert validation analyzed using Aiken’s V, user validity assessed through Pearson correlation, and reliability measured using Cronbach’s Alpha. Data analysis was conducted using Microsoft Excel and SPSS 16.0. The findings indicate that the developed instrument is highly valid, with an Aiken V value of 0.83 from expert validation. User validation resulted in 18 valid items and two invalid ones, while the reliability coefficient (Cronbach's Alpha) was 0.81, indicating high reliability. Consequently, 18 out of the 20 developed items are suitable for broader implementation. These findings provide a valuable tool for physics education lecturers and study programs in assessing students' environmental attitudes.